Pterygosomatid mites of a new species group ligare (Acariformes: Pterygosomatidae: Pterygosoma) parasitizing tree iguanas (Squamata: Liolaemidae: Liolaemus) - Fajfer, Monika; Acuña, Daniel González (Zootaxa, 2013)
A new species group, ligare, is established within the subgenus Pterygosoma (Acariformes: Pterygosomatidae: Pterygosoma) based on an analysis of female morphology. This group includes 6 newly described species—all from Liolaemus spp. (Squamata: Liolaemidae) from Chile: P. ligare sp. nov., P. formosus sp. nov., P. ovata sp. nov., and P. levissima sp. nov. from Liolaemus pictus; P. chilensis sp. nov. from L. chilensis, and P. cyanogasteri sp. nov. from L. cyanogaster. The ligare species group differs from other mites of the subgenus Pterygosoma by the presence of the movable cheliceral digit without a basal spur, solenidion ω of the palp tarsus, anterior mid-dorsal setae, large number of setae (about 200–300 pairs) on the lateral and the posterior parts of the idiosomal dorsum and the lateral parts of the idiosomal venter, by the idiosomal hypertrichy of ventro-median setae vm, setae 3a located outside of coxal fields II, the absence of setae 4b, the presence of paired setae tc and vs on tarsi III–IV, 5 setae on tibiae II–IV, 4 or 5 setae on genua I, II, 3 setae on genua III–IV, 5 setae on femur I, 5 or 4 setae on femur II and 3 setae on femur III. A key to females of the new species group is provided. Pterygosoma patagonica Dittmar de la Cruz, Morando and Avila, 2004 insufficiently described but showing most characterisitcs of ligare group is considered as nomen dubium.